Altered Steroidome in Women with Multiple Sclerosis - Kancheva, Radmila; Hill, Martin; Velíková, Marta; Kancheva, Ludmila; Včelák, Josef; Ampapa, Radek; Židó, Michal; Štětkářová, Ivana; Libertínová, Jana; Vosátková, Michala; Kubala Havrdová, Eva (International journal of molecular sciences, 2024)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) mainly afflicting young women. Various steroids can influence the onset and development of the disease or, on the contrary, mitigate its course; however, a systematic review of steroidomic changes in MS patients is lacking. Based on the gas chromatography tandem mass spectrometry (GC-MS/MS) platform and, in the case of estradiol, also using immunoassay, this study performed a comprehensive steroidomic analysis in 25 female MS patients aged 39(32, 49) years compared to 15 female age-matched controls aged 38(31, 46) years. A significant trend towards higher ratios of conjugated steroids to their unconjugated counterparts was found in patients, which is of particular interest in terms of the balance between excitatory and inhibitory steroid modulators of ionotropic receptors. Patients showed altered metabolic pathway to cortisol with decreased conversion of pregnenolone to 17-hydroxypregnenolone and 17-hydroxypregnenolone to 17-hydroxyprogesterone and increased conversion of 17-hydroxypregnenolone to dehydroepiandrosterone (DHEA), resulting in lower levels of 17-hydroxyprogesterone, as well as indications of impaired conversion of 11-deoxy-steroids to 11β-hydroxy-steroids but reduced conversion of cortisol to cortisone. Due to over-activation of hypothalamic-pituitary-adrenal axis (HPAA), however, cortisol and cortisone levels were higher in patients with indications of depleted cortisol synthesizing enzymes. Patients showed lower conversion of DHEA to androstenedione, androstenedione to testosterone, androstenedione to estradiol in the major pathway, and testosterone to estradiol in the minor pathway for estradiol synthesis at increased conversion of androstenedione to testosterone. They also showed lower conversion of immunoprotective Δ5 androstanes to their more potent 7α/β-hydroxy metabolites and had lower circulating allopregnanolone and higher ratio 3β-hydroxy-steroids to their neuroprotective 3α-hydroxy-counterparts.
Keywords: Humans; Tandem Mass Spectrometry; Case-Control Studies; lidé středního věku; Hydrocortisone; differential diagnostics; Multiple Sclerosis; hydrokortison; studie případů a kontrol; multivariate statistics; Female; dospělí; lidé; GC-MS/MS; steroidy; steroidomics; tandemová hmotnostní spektrometrie; Adult; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; multiple sclerosis; roztroušená skleróza; Middle Aged; Gas Chromatography-Mass Spectrometry; Steroids